Kualitas Pelayanan dan Kepuasan Pasien Rawat Jalan Pengguna Jaminan Sosial Kesehatan - Rizka Muliyani; Fatma Siti Fatimah; Raden Jaka Sarwadhamana (Jurnal Kesehatan Masyarakat Indonesia, 2022)
Background: Fair and equitable health service is one of the ways to fulfill the health right of each individual. Health service is one of the main priorities in Indonesia, it is one of the basic rights of society. The application for national health insurance under BPJS health is the beginning of health service changes. The monitoring of patient satisfaction levels is certainly a target for every agency or service provider organization, in this case, Puskesmas always evolves and can compete with other community health centers. Objective: To determine the correlation of service quality to the outpatients’ satisfaction of BPJS users at Puskesmas Kasihan 1 Bantul Regency. Methods: This type of research is quantitative analytic with a cross-sectional research design. The sample in this study is 112 respondents. The statistical test used is the spearman’s rank. Results: The results showed that there was a strong correlation related to the correlation service quality to outpatient satisfaction of BPJS users at Puskesmas Kasihan I Bantul Regency, where the correlation coefficient value is 0.710 with sig. 0.000. Conclusion: there is a relationship between service quality and satisfaction of outpatients using BPJS at the Kasihan 1 Public Health Center, Bantul Regency. The quality of service in the good category affects the level of patient satisfaction in the moderate category. The highest service quality dimension is the dimension of physical evidence (tangibles) compared to other dimensions.